Clinical features and outcomes of COVID-19 despite SARS-CoV-2 vaccination in people with multiple sclerosis. Issue 4 (October 2021) - Rose, Deja R; Mahadeen, Ahmad Z; Carlson, Alise K; Planchon, Sarah M; Sedlak, Jennifer; Husak, Scott; Bermel, Robert A; Cohen, Jeffrey A; Moss, Brandon P
Background: Several studies have demonstrated reduced serological response to vaccines in patients treated with anti-CD20 agents. However, limited data exist surrounding the clinical effect of disease modifying therapy (DMT) use on vaccine efficacy. Objectives: To investigate breakthrough coronavirus disease 2019 (COVID-19) in vaccinated people with multiple sclerosis (PwMS) on DMT. Methods: PwMS on DMT diagnosed with COVID-19 after full vaccination were identified from an existing Cleveland Clinic COVID-19 registry, supplemented by provider-identified cases. Demographics, disease history, DMTs, comorbidities, exposures, vaccination status, and COVID-19 outcomes were confirmed by review of the electronic medical record. Results: Thirteen (3.8%) of 344 fully vaccinated people with multiple sclerosis on disease modifying therapy were diagnosed with COVID-19 after vaccination. Ten patients (76.9%) were on an anti-CD20 therapy, the remaining 3 (23.1%) on fingolimod. Only 2 patients (15.4%), both on anti-CD20 therapy, required hospitalization and steroid treatment. Neither required Intensive Care Unit admission. Conclusion: Patients treated with anti-CD20 agents and sphingosine 1-phosphate receptor modulators may still be at risk for COVID-19 despite vaccination. While still at risk for hospitalization, intubation and death from COVID-19 appear rare. Larger studies analyzing how this may differ in the setting of emerging variants are needed.